Análise da colaboração científica dos programas de Pós-graduação em Ciência da Informação brasileiros - Justino, Thais da Silva (Universidade Federal de São Carlos, 2019)
There is a growing interest in metric studies on scientific collaboration in Brazilian postgraduate studies. However, a significant part of these studies are conducted from international bibliographic databases at the macro level, while other studies are limited to a particular Postgraduate Program (PPG), making comparative analysis and group mapping impossible. The general objective of this research comprises the elaboration of indicators on the national and international scientific collaboration of the PPGs of the Applied Social Sciences Area 1 - Information Science, recommended by CAPES of Brazil. The method comprised a quantitative approach of exploratory nature. Bibliometrics and social network analysis were used as analysis techniques. The sample analyzed comprised 519 bibliographic records referring to the scientific production of 421 permanent teachers who work in 27 PPG of the Applied Social Sciences Area 1 - Information Science, from 2013 to 2018. The results achieved included the elaboration of a set of indicators. involving: 1] production characterization by PPG, identifying the evolution and percentage of contribution; 2] identification of national and international scientific collaboration through co-authoring, highlighting initiatives with international institutions, the main vehicles of communication and the most investigated themes. It can be concluded that the results achieved can contribute to the improvement of the PPG and of the National Graduate System, by maximizing the understanding of collaboration in the area of Applied Social Sciences 1 - Information Science, by providing a set of indicators, elaborated from the fusion of metadata from two sources of information. Lattes and Web of Science, enabling the identification of the institutional links of the authors in relation to PPG and international institutions.
Scientific analysis of collaboration of brazilian Information Science postgraduate programs
Keywords: Colaboração científica; Indicadores de ciência e tecnologia; Redes de colaboração científica; Programas de Pós-graduação; Ciência da Informação; Scientific collaboration; Scientific collaboration networks; Science and technology indicators; Postgraduate programs; Information Science; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::TEORIA DA INFORMACAO